O cinema de Ingmar Bergman: a construção dos elementos estilísticos e existencialistas em Gritos e Sussurros - Hellen Silvia Marques Gonçalves (2019)
This research aims to analyze the creation of the audio and visual stylistic elements from a sample of the extensive cinematographic work of Ingmar Bergman, approaching them to the existentialist theory, seeking to understand how the filmmaker discusses certain philosophic concepts through his characters and narratives, and the interaction between image and audio. In order to do so, the scientific clipping established as the primary font was the movie Cries and Whispers (1972), considering that this work is distinguished by the return of the proximity between the swedish filmmaker and the existentialism of Søren Kierkegaard, becoming an exception amid the agnostic existentialism that prevailed during almost twenty years in bergman's filmography, between 1963 and 1981. Firstly the premises of Marc Ferro were discussed to analyze the swedish mentality, that permeated the director accordingly to what was pursued and applied in his cinematography, enhancing the influence of romantic swedish and slavic tradition, in literature and painting. In this regard, pictoric images, the soundtrack, conceptual coordinates and the existentialist foundations of the movie were analyzed. Therefore, from researching the stylistic elements brought up by Bergman, a chain of possibilities that relate his work to kierkegaardian philosophy, displaying how the characters stand in the stages of the life path exposed by the danish philosopher.